ANALYSIS OF GOMBANG AT VILLAGE MESKOM SUB-DISTRICT OF BENGKALIS DISTRICT BENGKALIS RIAU PROVINCE - Rohani, Setia; Yulinda, Eni; Hamid, Hamdi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The Research on the analysis of gombang was conducted in December until January 2015 in Village Meskom Sub-District of Bengkalis District Bengkalis Riau Province. The aims of this study were to great investmens, gross income, net income and feasibillity using gombang. The method used to this case survey, respondents were selected through stratified Random Sampling of gombang of 3,4 and 9 bags.The results of this study indicate that investmens gombang 3 bags Rp 9.755.000, 4 bags Rp 12.505.000 and 9 bags Rp 26.655.000. Gross income gombang 3 bags Rp 89.496.000, 4 bags Rp 132.660.000 and 9 bags Rp 236.808.000. Net Income gombang 3 bags Rp 63.695.000, 4 bags Rp 101.115.000 and 9 bags Rp 181.079.000. Feasibility of gombang for 3 bags RCR 3,46 and PPC 1,43. 4 bags RCR = 4,20 and PPC = 1,08, 9 bags RCR = 4,25 and PPC = 1.4. This shows that effort gombang gear profiable and feasibilty to proceed.Keywords : Gombang, investment, income, feasibility